2017
DOI: 10.1002/ejlt.201700320
|View full text |Cite
|
Sign up to set email alerts
|

Production of MLM Type Structured Lipids From Grapeseed Oil Catalyzed by Non‐Commercial Lipases

Abstract: Low calorie triacylglycerols (TAG) presenting medium-chain fatty acids (M) at positions sn-1,3 and long-chain fatty acids (L) at position sn-2 are known as MLM. This study aims at the production of MLM by acidolysis of grapeseed oil with medium-chain caprylic (C8:0) or capric (C10:0) acids. Grapeseed oil is used as source of long-chain polyunsaturated fatty acids (FAs), especially linoleic acid, at sn-2 position in TAG. Reactions are performed in batch, in solvent-free systems, during 48 h. Novel non-commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…With Lipozyme TL IM ® and Novozym 435 ® , the results of the present study are close to those described by Nunes et al (2011): 28.8 mol% and 30.4 mol% of incorporation, respectively. The acidolysis of grapeseed oil with caprylic or capric acid was also performed in solvent-free media, using non-commercial sn-1,3 regioselective lipases namely: the recombinant lipase from Rhizopus oryzae immobilized in Amberlite™ IRA 96 and Carica papaya lipase self-immobilized in papaya latex (Costa et al, 2018). Yields of new TAGs were between 38 and 69 mol%, after 48 h acidolysis at 40°C, molar ratio fatty acid:oil of 2:1.…”
Section: Incorporation Degree Of Capric and Caprylic Acidsmentioning
confidence: 99%
See 2 more Smart Citations
“…With Lipozyme TL IM ® and Novozym 435 ® , the results of the present study are close to those described by Nunes et al (2011): 28.8 mol% and 30.4 mol% of incorporation, respectively. The acidolysis of grapeseed oil with caprylic or capric acid was also performed in solvent-free media, using non-commercial sn-1,3 regioselective lipases namely: the recombinant lipase from Rhizopus oryzae immobilized in Amberlite™ IRA 96 and Carica papaya lipase self-immobilized in papaya latex (Costa et al, 2018). Yields of new TAGs were between 38 and 69 mol%, after 48 h acidolysis at 40°C, molar ratio fatty acid:oil of 2:1.…”
Section: Incorporation Degree Of Capric and Caprylic Acidsmentioning
confidence: 99%
“…The specificity of this lipase is directly related to the size of the fatty acid chain, and the enzyme has a preference for fatty acids with longer carbon chain (Rodrigues & Fernandez-Lafuente, 2010a;Rodrigues & Fernandez-Lafuente, 2010b;Caballero et al, 2014). On the contrary, the recombinant lipase of Rhizopus oryzae immobilized in Amberlite IRA 96 showed a preference towards caprylic acid while Carica papaya lipase self-immobilized in papaya latex showed no preference towards caprylic or capric acid (Costa et al, 2018).…”
Section: Incorporation Degree Of Capric and Caprylic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khodadadi et al ( 43 ) also reported that Lipozyme TL IM and Novozyme 435 were more effective in transesterification reaction between flaxseed oil and tricaprylin than Lipozyme RM IM and Amano DF. Table 1 ( 44 , 48 - 53 ) summarizes the utilization of immobilized lipase for MLM lipase synthesis.…”
Section: Enzymes For Mlm Structured Lipid Synthesis: Types Ans Sourcesmentioning
confidence: 99%
“…Coffee is one of the most consumed beverages in the world and global consumption of 161 million of 60 kg coffee bags per year. So, there is a production of coffee byproducts such as coffee silverskin (CS) [1][2][3]. The CS is the thin tegument that covers the two coffee seeds and it is the only byproduct generated during green bean roasting and represents about 4.2 % (w/w) of coffee beans.…”
Section: Introductionmentioning
confidence: 99%